2016
DOI: 10.5603/kp.a2015.0175
|View full text |Cite
|
Sign up to set email alerts
|

Global cardiovascular mortality risk in the adult Polish population: prospective assessment of the cohorts studied in multicentre national WOBASZ and WOBASZ Senior studies

Abstract: A b s t r a c t Background and aim:To develop a global cardiovascular disease (CVD) mortality risk model for the Polish population and to verify these data in the context of the SCORE risk algorithm. Methods:We analysed data obtained in two multicentre national population studies, the WOBASZ study which was conducted in [2003][2004][2005] and included 14,769 subjects aged 20-74 years, and the WOBASZ Senior study which was conducted in 2007 and included 1096 subjects above 74 years of age. All these subjects we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 6 publications
0
11
0
Order By: Relevance
“…According to the survey results, established diabetes was reported by 6.4% of women and 6.9% of men [5]. However, this relationship is inverted in elderly subjects since, as shown in the WOBASZ Senior study conducted in subjects ≥ 75 years of age, the prevalence among women is higher than that among men [7]. In general, the risk of type 2 diabetes mellitus increases with age, with the prevalence in subjects above the age of 50 significantly exceeding the all-population mean (data on file [3,4,8]).…”
Section: Discussionmentioning
confidence: 99%
“…According to the survey results, established diabetes was reported by 6.4% of women and 6.9% of men [5]. However, this relationship is inverted in elderly subjects since, as shown in the WOBASZ Senior study conducted in subjects ≥ 75 years of age, the prevalence among women is higher than that among men [7]. In general, the risk of type 2 diabetes mellitus increases with age, with the prevalence in subjects above the age of 50 significantly exceeding the all-population mean (data on file [3,4,8]).…”
Section: Discussionmentioning
confidence: 99%
“…Poland is a country with high exposure to CVD risk factors [25][26][27][28]. The most frequent CVD risk factors in Poland are hypercholesterolaemia, hypertension, and cigarette smoking [29]. Our results Carotid-femoral pulse wave velocity and the SCORE system are in accordance with another study which demonstrated that arterial stiffness (assessed by CFPWV among other parameters) was also positively associated with SCORE, but in that study the authors did not attempt to assess a cut-off point for CFPWV, which allowed to classify the participants into the high and low CVD risk groups [22].…”
Section: Discussionmentioning
confidence: 99%
“…The primary objective of the survey was the assessment of cardiovascular diseases in this population [12]. A two-staged sampling scheme was used, stratified according to provincial and district categories (2 small districts, 2 medium and 2 large districts from every province).…”
Section: Methodsmentioning
confidence: 99%